Evidence for reciprocal network interactions between injured hearts and cancer - Guler, Melisa N.; Tscheiller, Nathalie M.; Sabater-Molina, Maria; Gimeno, Juan R.; Nebigil, Canan G. (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) and cancer are responsible for 50% of all deaths in middle-aged people. These diseases are tightly linked, which is supported by recent epidemiological studies and case control studies, demonstrating that HF patients have a higher risk to develop cancer such as lung and breast cancer. For HF patients, a one-size-fits-all clinical management strategy is not effective and patient management represents a major economical and clinical burden. The cardiotoxic effects of anti-cancer treatment leading to HF have been extensively studied. Indeed, even before the initiation of cancer therapy, cancer patients displayed impairment in the CV function and exercise capacity. Moreover, the optimal cardioprotective and surveillance strategies should apply to cancer patients with pre-existing HF. Understanding of HF and cancer communication can be a new alternative to deeply understand molecular mechanisms of HF-cancer interaction that defines profiles of bilateral signal networks, and identifies disease-specific biomarkers and therapeutic targets. Recently, preclinical studies addressed the hypothesis that there is bilateral interaction between cardiac injury and cancer development. Here we will discuss the preclinical evidence on bilateral connection between cardiac injury (HF and early cardiac remodeling) and cancer through secreted factors. In current daily practice, there is nearly no awareness that new-onset cancer can develop in patients with heart failure, and the results of this study will spark interest in this hitherto unexplored disease combination. We speculate that it may be recommended to consider differential surveillance programs to screen patients with HF who are at risk for cancer development.